Analysis of the Relationship Between Promotion and Brand Image on Consumer Purchase Interest (Case Study: Mie Gacoan Solo) - Risma Maharani, Novita (LPPM Universitas Duta Bangsa Surakarta, 2023)
The intense competition among entrepreneurs, especially in the culinary sector, demands that companies continuously sustain and grow. It is challenging for a company to retain existing customers and attract new ones without a positive and strong brand image. In addition to a good brand image, another marketing strategy that plays an important role in attracting consumer purchase interest is promotion. This study focuses on Mie Gacoan, specifically the Solo branch. Mie Gacoan is a well-known spicy noodle restaurant with many branches across Java and Bali. The restaurant is popular among various groups, especially the younger generation, as the noodles offered have a distinct spicy flavor, drawing the interest of young people to try them. This study uses a descriptive qualitative method, with a population consisting of the residents of Solo Raya, totaling 526,870 people who have consumed Mie Gacoan and are willing to complete a questionnaire. The results of the study show that promotion and brand image influence consumer purchase interest in Mie Gacoan's Solo branch.